Universality of Man as a Cultural and Historical Human Being - S. Z. Gontcharov (Russian State Vocational Pedagogical University, 2015)
On the grounds of theoretical synthesis, the paper reveals the phenomenon of human being in its creative dimension. The present research is aimed at exploring the prospective opportunities for academic processes. The basics of universal essence of man as a cultural historic being with unlimited potential of self- development are defined; the man being mirrored by the basic philosophic concepts: naturalistic, orthodox-oriented, bio-social or bio-socio-cultural. There are two opposing views on human nature: the anthropological essentialism holding that individuality is predetermined by essence; and the anthropological existentialism claiming the opposite - human existence precedes the essentiality, the latter being constituted by the acts of choice, self-development and self-responsibility for personal choice and projecting. In the first case, the subjective side of human existence is ignored, while in the second - the objective socially conditioned side is left behind. Both theories are antihistorical as it is the history that conditions the essence of man according to the ancestral determination, the latter being modified by way of human activity and communication in a particular historical period. The components of human universal essence are defined as follows: possession of organic body, social heritage, free will, self-activity, creativity, social and rational human nature, absence of antagonistic programs of social behavior. According to the author, for the adequate realization of human universality, it is necessary to move from the profit oriented speculative market economy to the creative one oriented on social effectiveness, quality of life and reproduction of wholesome individuals. The research output can be used for devising the methodology of philosophic and pedagogic anthropology, as well as pedagogic practices of teaching philosophy and pedagogic theory in higher school.